Cloud computing basics - Srinivasan, S. (SpringerBriefs in Electrical and Computer Engineering, 2014)
Cloud Computing Basics covers the main aspects of this fast moving technology so that both practitioners and students will be able to understand cloud computing. The author highlights the key aspects of this technology that a potential user might want to investigate before deciding to adopt this service. This book explains how cloud services can be used to augment existing services such as storage, backup and recovery. Addressing the details on how cloud security works and what the users must be prepared for when they move their data to the cloud. Also this book discusses how businesses could prepare for compliance with the laws as well as industry standards such as the Payment Card Industry.